A CASE STUDY OF STUDENT LEARNING DIFFICULTIES ON SOCIAL STUDIES LEARNING IN CLASS V SDN 11 RIO PAKAVA DURING THE COVID-19 PANDEMIC - Diah Septiyani; Pahriadi Pahriadi (Jurnal Dikdas, 2021)
The purpose of this research is to reveal the factors that cause students to have learning difficulties in social studies learning as well as to find out the teacher's efforts in overcoming students who have learning difficulties in social studies learning. This research is a case study descriptive research and is located in the fifth grade of SDN 11 Rio Pakava. The results showed that the causes of student learning difficulties were the lack of teacher treatment in providing reading materials on social studies subjects, the lack of use of social studies learning media, and lack of parental attention if the students got low grades, readiness, interest, intelligence of students in following subjects. Social studies lessons, and physical disabilities suffered by students and Efforts made by teachers to overcome learning difficulties, namely conducting learning using learning models, using image media, providing additional lessons according to the subject in question, giving homework and remedial teaching.